Метакогнитивная репрезентация концептуальной области „кажимости” (на материале семантики глагольных предикатов „казаться”, „показаться”) - Чернцова, Елена (Studia Rossica Posnaniensia, 2019)
The article analyzes the correlation between the cognitive semantics of the words казаться, показаться and the ordinary/fictional narrative strategy, embodied in a context of a particular type. The cognitive semantics of the words is identified within such parameters as a ‘discourse context type’, ‘narrative strategy’, as well as the ‘communicative register’ – either ‘reproductive’ or ‘informative’. The paper considers a gestalt scenario, according to which different contexts with the words казаться, показаться are built up. The author demonstrates the integrity of the gestalt and also describes focus shifts which underlie the construction of different contexts – ‘background’ and ‘figure’.